1972
DOI: 10.1111/j.1755-3768.1972.tb05956.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on Morphology and Function of the Drainage Area of the Eye of Man

Abstract: I n meridional sections, the anterior chamber angle is characterised by the width of the entrance into the angle, the shape of the apex, the configuration of the angle recess, and the position of the anterior part of the ciliary body. There are considerable variations in the morphology of the canal of Schlemm. The most important characteristics of the canal include the position of the sinus as regards the apex of the anterior chamber angle, the width of its lumen, and the inclination of the canal of Schlemm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…In addition, Nesterov et al found that the posterior SC, where received the most force from scleral spur, is wider than the anterior SC. This result also confirmed the importance of scleral spur on the morphology of SC [21]. Thus, in consideration of the close relationship between SC and scleral spur [16][17][18][19][20][21], and the close relationship between SC and aqueous humor outflow resistance [5][6][7][8][9], previous studies have suggested that short scleral spur could be engaged in the pathogenesis of POAG [16,22,23].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, Nesterov et al found that the posterior SC, where received the most force from scleral spur, is wider than the anterior SC. This result also confirmed the importance of scleral spur on the morphology of SC [21]. Thus, in consideration of the close relationship between SC and scleral spur [16][17][18][19][20][21], and the close relationship between SC and aqueous humor outflow resistance [5][6][7][8][9], previous studies have suggested that short scleral spur could be engaged in the pathogenesis of POAG [16,22,23].…”
Section: Introductionsupporting
confidence: 72%
“…1a): the red solid line (a curved line bisecting the width of the scleral spur at every point) represents scleral spur length, drawn from the tip of the scleral spur to the middle of the red dotted line, which connects the anterior and posterior points where the sclera curves out to form the spur (located near the posterior end of SC, to the point where the sclera begins again). Method II (Nesterov and Batmanov [21,23,24]) ( Fig. 1b): the scleral spur length measurement (the red solid line) was taken from the tip of the scleral spur, directly to the level of the posterior end of SC.…”
Section: The Measurements Of Scleral Spur and Sc Parametersmentioning
confidence: 99%
“…The rationale is to remove the largest portion of resistance to outflow exerted by the juxtacanalicular portion of the trabecular meshwork and the inner wall of Schlemm's canal. [3][4][5] In fact, better aqueous percolation is achieved during ab externo nonpenetrating filtering surgery by peeling the inner wall of Schlemm's canal. 6 Ab interno trabeculectomy is a novel trabecular procedure that, when associated with phacoemulsification, has been shown to produce a clinically significant decrease in IOP in eyes with a poor prognosis for filtration surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Schlemm's canal is a single endothelium-lined canal that surrounds the cornea. Schlemm's channel cells have characteristics that are similar to blood and lymphatic vessels, as well as molecular similarities between the two cell types [3]. With three views, the size of the cross section of Schlemm's canal was estimated at 1709 m; The cross-sectional area is now expected to vary between 4064 and 7164 m, with many branching water channels.…”
Section: Figure 1 Flow Of Aqueous Humor In Eyementioning
confidence: 99%